1998
DOI: 10.1097/00005537-199803000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Anthrapyrazoles and Interstitial Laser Phototherapy for Experimental Treatment of Squamous Cell Carcinoma

Abstract: Interstitial laser therapy (ILT) is an effective palliative treatment for advanced head and neck cancer, but recurrence often is seen at the margin. The objective of the current study was to test combined drug and laser therapy as an experimental approach for improved treatment of human squamous cell carcinoma (SCCA). Human SCCA tumor transplants were grown in nude mice and injected with the photosensitive anthrapyrazole CI-941 before ILT. Intralesional drug injections alone at levels ranging from 60 to 1200 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
(28 reference statements)
1
10
0
Order By: Relevance
“…This was the first effort in the literature to explore the concept of local injection of anti-cancer drug combined with laser interstitial therapy for cancer treatment. Additional testing in a larger group of animals in Germany by Graeber et al (1998) confirmed these results, which provide strong preclinical evidence in support of the hypothesis that photo chemotherapy may be an alternative treatment for human tumors. Similar LITT studies have followed with a translational experimental model combining intratumor cisplatin with Nd:YAG laser for thermal ablation of recurrent and advanced head and neck cancer (Paiva et al, 1998b;Graeber et al, 1999).…”
Section: Photo-chemical and Photo-thermal Activation Of Anti-cancer Dsupporting
confidence: 60%
See 1 more Smart Citation
“…This was the first effort in the literature to explore the concept of local injection of anti-cancer drug combined with laser interstitial therapy for cancer treatment. Additional testing in a larger group of animals in Germany by Graeber et al (1998) confirmed these results, which provide strong preclinical evidence in support of the hypothesis that photo chemotherapy may be an alternative treatment for human tumors. Similar LITT studies have followed with a translational experimental model combining intratumor cisplatin with Nd:YAG laser for thermal ablation of recurrent and advanced head and neck cancer (Paiva et al, 1998b;Graeber et al, 1999).…”
Section: Photo-chemical and Photo-thermal Activation Of Anti-cancer Dsupporting
confidence: 60%
“…Ongoing clinical studies are being conducted to determine the impact that this alternative approach of combining laser and anti-cancer agents may have on the control of disease, survival and quality of life in cancer patients (Paiva et al, 2005b;Paiva et al, 2005c). In addition to the advantage of photo-activation, several of these light sensitive chemotherapeutic agents have been reported to exhibit enhanced toxicity in tumor cells after photo-thermal-activation (Chung et al, 2003;Graeber et al, 1999;Graeber et al, 1998;Paiva et al, 1995;Saxton et al, 1996). As a result, a potentially useful and less invasive approach for treatment of malignancies is to combine imaging guided interstitial laser surgery with conventional chemotherapy (Paiva et al, 2005b;Saxton et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…KTP laser light also has been used surgically after coupling to a bare fiber in both the contact mode and noncontact mode with reported clinical effectiveness in controlling bleeding disorders as well as tongue and soft palate cancer resections in addition to laryngeal cancer treatment [21,22]. KTP laser fiberoptics recently were tested for interstitial treatment of transplanted human squamous-cell tumors after injection of the anthrapyrazole CI-941 [9,10]. This agent was selected as a more photosensitive and less toxic anthracycline-related drug than daunomycin for initial in vivo studies of human squamous-cell carcinoma transplants in nude mice [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…This agent was selected as a more photosensitive and less toxic anthracycline-related drug than daunomycin for initial in vivo studies of human squamous-cell carcinoma transplants in nude mice [23,24]. The results showed a significantly improved cure rate of 72% after drug and laser therapy compared to 46% for laser treatment alone [10]. Delayed tumor regrowth and prolonged mean survival was seen after laser chemotherapy compared to either KTP laser alone or CI-941 injection alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation